Oral drug delivery - Rai, Vineet Kumar (Henry Stewart Talks, 2022)
Advantages and disadvantages of oral drug delivery, Gastrointestinal tract anatomy and function, GI tract components, Challenges in oral drug delivery, Pharmaceutical factors to be considered, Patient-related factors to be considered, Suitable dosage forms